ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA GO PUBLIC PADA BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2011-2014 - Indradewi, Citra; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to analyze the effect of working capital management on profitability of basic industry and chemicals that listed in Indonesia Stock Exchange (IDX) within 2011-2014. Indicator of working capital management used in this research are cash conversion cycle (CCC), receivable conversion period (RCP), inventory conversion period (ICP), payable deferral period (PDP), and current ratio (CR). On the other hand, indicator of profitability used in this research is net profit margin (NPM). The sample data used in this research took from financial statement that have been audited and published in IDX. According to sampling technique used in this research, which is purposive sampling, there’re 25 companies that fit to certain criteria. Method of data analysis used in this research is Multiple Regression Analysis, which previously performed classical assumption test. Hypothesis test is using F-statistic test, t-statistic test, and determination of coefficients with significance level of 5%.The result of this research indicates independent variables simultaneously (F-statistic test) effect on profitability (NPM) with significance level 0,000. On the other hand, partially (t-statistic test) indicates CCC has negative and significant effect on profitability, PDP and CR have positive and significant effect on profitability. Meanwhile, RCP and ICP has positive and not significant effect on profitability. Adjusted ’s score is 0,454 which means that the ability of independent variables can explain profitability with 45,4%, while the rest is explain by other factors.